ANALISIS DETERMINAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) PADA WANITA USIA SUBUR (WUS) DI KECAMATAN MUARA PADANG KABUPATEN BANYUASIN - Yuliana Yuliana; Rico Januar S; Dianita Ekawati (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: Cervical cancer is the second most common patient after breast cancer. Prevention of cervical cancer can be done by carrying out early cervical health checks (screening), because the symptoms of cervical cancer are not visible until a more severe stage. Early detection of cervical cancer with VIA is a visual examination of the cervix using vinegar. This study aims to analyze the determinants of the Visual inspection of Acetic Acid (IVA) in Women of Childbearing Age (WUS) in Muara Padang, Banyuasin District. Methods: This research is an analytical survey with Cross Sectional design. The population in this study is all women of childbearing age (WUS) who live in Muara Padang Subdistrict banyuasin district which amounts to 9049 people. The samples in this study were some women of childbearing age (WUS) who resided in Muara Padang Subdistrict banyuasin and sampling by Sistematic Random Sampling method. So the large sample in this study was 190 People. Results: : The results of the study obtained there is a significant relationship between knowledge and Visual Inspection Examination of Acetic Acid (IVA) in Women of Childbearing Age (WUS) In Muara Padang Subdistrict, Banyuasin Regency (p value 0,014). Conclusion: Factors related to the Visual Inspection of Acetic Acid (IVA) in Women of Childbearing Age (WUS) in Muara Padang District, Banyuasin Regency, is the knowledge factor. It is expected that the public can increase their knowledge of the importance of Acetic Acid Visual Inspection Examination (IVA) as well as husband and family support in cervical cancer prevention